2015
DOI: 10.1017/iop.2015.21
|View full text |Cite
|
Sign up to set email alerts
|

Amazon Mechanical Turk for Industrial and Organizational Psychology: Advantages, Challenges, and Practical Recommendations

Abstract: m t urk a dva n tag e s , c ha l l e ng e s , a n d r e c om m e n dat ion s 171 workers are appropriate or inappropriate samples for research questions relevant to the field of I-O psychology. MTurk is a potentially valuable source of data for I-O psychologists, and as such, we need to examine and explore it more fully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 24 publications
0
45
0
Order By: Relevance
“…Taken together, our conclusions echo the conclusions of other researchers (cf., Behrend et al, 2011 ; Buhrmester et al, 2011 ; Berinsky et al, 2012 ; Casler et al, 2013 ; Brandon et al, 2014 ; Woo et al, 2015 ): MTurk samples are not representations of the general population. We should carefully consider whether representativeness of national data should be the criterion, as organizational researchers have traditionally collected data from class settings (e.g., MBA or undergraduate), specific organizations/communities, and even other online panel data from survey companies where participant solicitation processes are not transparent.…”
Section: A Systems Perspective For Evaluating Mechanical Turkmentioning
confidence: 99%
“…Taken together, our conclusions echo the conclusions of other researchers (cf., Behrend et al, 2011 ; Buhrmester et al, 2011 ; Berinsky et al, 2012 ; Casler et al, 2013 ; Brandon et al, 2014 ; Woo et al, 2015 ): MTurk samples are not representations of the general population. We should carefully consider whether representativeness of national data should be the criterion, as organizational researchers have traditionally collected data from class settings (e.g., MBA or undergraduate), specific organizations/communities, and even other online panel data from survey companies where participant solicitation processes are not transparent.…”
Section: A Systems Perspective For Evaluating Mechanical Turkmentioning
confidence: 99%
“…Studies can be conducted simultaneously in a large number of languages and cultures, a strategy not scalable in other settings. MTurk enables researchers to apply multiple levels of screeners in order to target specific respondents, including on geography, demographics, and language-an approach that is simply not possible in other research settings (Rouse, 2015;Steelman et al, 2014;Woo et al, 2015). Generally, no.…”
Section: The Convenience Critique: the Myth Of The Organizational Stumentioning
confidence: 99%
“…Nonetheless, the results of the current study and prior studies offer further evidence that this is a problem faced by scholars who collect data through MTurk. As noted by Woo, Keith, and Thornton (), “…researchers should avoid using MTurk when the participant anonymity creates a strong possibility for dishonest responses or when the entire study would be made invalid if the participants’ self‐reported identities were false…” (p. 176). The problem of imposters should not be interpreted as a reason to avoid MTurk, as there are many advantages to its use (e.g., diverse samples; Krupnikov & Levine, ).…”
Section: Discussionmentioning
confidence: 99%